Practical Bootstrap : learn to develop responsively with one of the most popular CSS frameworks - Matsinopoulos, Panos (Apress, 2020)
Learn to use one of the most popular CSS frameworks and build mobile-friendly web pages. Used for numerous websites and applications, Bootstrap is a key tool for modern web development. You will explore the grid system and then be introduced to the power of Bootstrap in practical projects. Youll make navigation bars, use themes and styling, create and manipulate cover pages, admin dashboards, forms, and modal dialogs. Youll learn to use Scrollspy and create tooltips and popovers. The modern web is responsive and Bootstrap continues to be one of the most popular CSS frameworks available to modern web professionals. Learn by doing with this book today. You will: Review how the grid system applies to Bootstrap Create stunning cover pages that encompass a large background image Build an admin dashboard page that changes its layout according to a devices display width Work with the modal HTML markup and its main parts Customize modal behavior by setting various options using JavaScript Integrate Bootstrap JavaScript libraries with your own HTML page Add scroll spying functionality to your long-content pages Adjust the offset and activation point of the scroll sections.